MOOCs on the Context of Software Engineering Teaching and Training: Trends and Challenges - Prates, Jorge Marques (2018)
This Research Full Paper presents an analysis of the challenges and advantages on applying MOOCs in software engineering teaching and training contexts. Software engineering is a constantly evolving discipline in which educators are involved with a constant flow of new tools, resources and techniques in software development. This scenario makes the act of teaching and contributing to the students' academic education more complex. The insertion of educational technologies brings contributions in this context, causing a transformation in the current scenario of teaching. An example of these new technologies are the MOOCs (Massive Open Online Courses) - open and online courses that are available in providers in partnership with reputable universities. Considering this scenario, this paper aims at identifying the challenges and trends of MOOCs application in software engineering domain, by means of a systematic mapping of the literature (SML). During the SML it was performed an analysis of 5100 papers and selection of 96 primary studies. The outcomes indicate that there is a potential in using MOOCs on teaching or training, as they are an alternative to offer courses applying traditional methods of learning. In addition, the challenges of this direction are analyzed and discussed.